Characterisation and monitoring of postoperative respiratory depression: current approaches and future considerations. (September 2019) - Ayad, Sabry; Khanna, Ashish K.; Iqbal, Sheikh U.; Singla, Neil
Summary: Respiratory depression is common in patients recovering from surgery and anaesthesia. Failure to recognise and lack of timely institution of intervention can lead to catastrophic cardiorespiratory arrest, anoxic brain injury, and mortality. Opioid-induced respiratory depression (OIRD) is a common and often under-diagnosed cause of postoperative respiratory depression. Other causes include residual anaesthesia, residual muscle paralysis, concurrent use of other sedatives, splinting from inadequate pain control, and obstructive sleep apnoea. Currently used methods to identify and monitor respiratory safety events in the post-surgical setting have serious limitations leading to lack of universal adoption. New tools and technologies currently under development are expected to improve the prediction of respiratory depression especially in patients requiring opioids to alleviate acute postoperative pain. In this narrative review, we discuss the various causes of postoperative respiratory depression, and highlight the advances in monitoring and early recognition of patients who develop this condition with an emphasis on OIRD.